Forecast of Biotechnology Trends in the World and in Ukraine Based on Analysis of Publications and Patents - Poliakova, O.Yu.; Shlykova, V.O.; Buntov, I.Yu. (Science and Innovation, 2024)
Introduction. Modern biotechnology is among the top priorities in every advanced economy. Problem Statement. Successful management of technology development requires an unbiased analysis of scholarly research results and their forecasting. The correspondence of technological development to the world trends plays an important role in ensuring the economy’s competitiveness. Purpose. The purpose of the study is to determine the world trends in scholarly research and developments in the field of biotechnology, as well as the correspondence of the situation in Ukraine to the world trends. Materials and Methods. Bibliometric and patent analysis is one of the most common tools for analyzing the current state, promising directions of scholarly research and commercial use. This research presents the results of analysis of the world and Ukrainian trends in publication and patent activities in the sphere of biotechnology for 2000-2015, as well as forecasts for 2016-2019. The trend models have been constructed for forecasting. Biotechnology-related publications of SCImago Journal & Country Rank portal, Science Direct database, and Vernadsky National Library of Ukraine abstract database, as well as patents of the World Intellectual Property Organization database have been used. Results. The forecast results have shown an upward tendency in the global amount of publications and patents in biotechnology, in the coming years. In all areas of biotechnology, the share of Ukrainian publications in the global space of biotechnological research is extremely small. Among the analyzed areas, the largest forecasted share of Ukrainian origin publications in international databases belongs to Materials Science — Biomaterials and amounts to 0.3% on the global scale. The patenting of Ukrainian developments at the international level, provided the existing trend is maintained, will also remain at a very low level (0.05% on a global scale). China and the USA, which have a share of 33.1 and 24.9%, respectively, will keep leadership in this direction The total number of patents belonging to the EU Member States (28) will reach about 18.1%. Conclusions. For today, Ukraine has certain advantages in the development of biotechnology in the field of agriculture, which can become the basis for the development of national bioeconomy. Consequently, in the agricultural sector, state support is needed to implement the existing developments by encouraging business. At the same time, in the medical field, there is a significant gap between Ukraine and the leading countries, thus the government should focus efforts on supporting research in this area in order to make its results ready for patenting.